Recognition of Physical Education Learning at Elementary School Level During the Covid 19 Pandemic in Jombang Regency - Saputro, Arnaz Anggoro; Prasetyo, Guntum Budi; Saputra, Yudi Dwi (PHEDHERAL, 2021)
The purpose of this study was to determine the implementation of physical education learning at the elementary school level during the COVID-19 pandemic in Jombang Regency. This research is a quantitative descriptive study using one variable without making comparisons with other variables. The method used is a survey using questionnaires and documentation. The population of the study was all the sports teachers in the Physical Education MGMP members as many as 130 teachers throughout Jombang Regency. The research sample was 100 out of a total of 130 sports teachers in Jombang who were randomly selected according to the percentage of the total number of teachers. The measuring instrument used in the variable of the implementation of physical education learning is a questionnaire with a Likert scale which has a weighted score of 1-5. The research sample filled out the questionnaire given by checking the column and assigning weights according to the five alternative answers provided, ranging from strongly agree, agree, hesitate, disagree, and strongly disagree. The scale for statements is favourable and unfavorable. The results showed that the level of implementation of physical education learning at the elementary school level during the COVID-19 pandemic, all elementary school sports teachers in Jombang Regency were in the "very low" category of 8% (8 teachers), "low" of 15.0% (15 teachers), “medium” by 46% (46 teachers), “high” by 26.0% (26 teachers), and “very high” by 5% (5 students). Based on the average score, which is 89.62, the identification of the implementation level of physical education learning at the elementary school level during the COVID-19 Pandemic Period, all elementary school sports teachers in Jombang Regency were at the "medium" level.